PENGARUH PERJANJIAN KARTEL ASING " Zerro Dollar Tour" TERHADAP BISNIS PARIWISATA DI BALI - Gede Bayu Surya Putra Pratama (2021)
A business competition is one of propotion thing that happen in native of business competition system, it could be categorized as serious infraction in world of law business and competition which is has impact of cartel that bring disadvantage to people especially consumer and cause instability of prices. Years to years any of enforcement to cartel case has been done due to impact of tenders accesary, but still ineffectively. Some difficulties of resistance has leverage to enforce the law, such as regulations of business competition that has no existence of indirect evidence, and lead forward to practice of court a differences that related on legal standing in procedural of law system. The regulation of business competition is not giving any authority for supervise to have search and confiscation for KPPU to obtain any documents as part of proof evidences process. However, the meaning of cartel as an agreement of cartel has limit on act in contract assessment.